Comparison of the Spinels Co3O4 and NiCo2O4 as Bifunctional Oxygen Catalysts in Alkaline Media. (10th January 2016) - Pletcher, Derek; Li, Xiaohong; Price, Stephen W.T.; Russell, Andrea E.; Sönmez, Turgut; Thompson, Stephen J.
Abstract: Data from experiments with both rotating disc electrodes (RDEs) and gas diffusion electrodes (GDEs) are used to investigate the properties of the spinels, Co3 O4 and NiCo2 O4, as bifunctional oxygen electrocatalysts. Emphasis is placed on catalyst compositions and electrode structures free of carbon. Oxygen evolution and reduction occur at surfaces where the transition metals are in different oxidation states but the surface can be repeatedly cycled between these two states without significant change. It is shown that carbon-free, NiCo2 O4 catalysed GDEs can be fabricated using structures based on stainless steel cloth or nickel foam. Those based on nickel foam can be cycled extensively and allow both O2 evolution and reduction at current densities up to 100 mA cm −2 .